Policy Implementation of One-Price Fuel Oil Distribution: An Empirical Study in Indonesia - Milwan, Milwan; Kurniawan, Hary; Adhy, M. Entang; Udin, Udin (International Journal of Energy Economics and Policy, 2020)
This study aims to analyze the factors that influence the implementation of one-price fuel oil distribution based on the theory of Meter and Horn (1975), namely policy standards and objectives, resources, communication between organizations, characteristics of implementing agencies, economic, socialization and political environment, and attitude of the implementers. This study uses qualitative methods. By using purposive sampling, data are collected through interviews, documentation, and field observations. Data further are analyzed using data reduction, data presentation, and concluding. The results show that the implementation of one-price fuel oil distribution in Indonesia had generally been running effectively, but in some areas, there are still many obstacles. In addition to road constraints, the arises problem often is the constraints of human resources involved in the distribution of fuel oil, where the implementers carry out their activities outside of the predetermined standard operating procedures. To overcome this obstacle, the oil fuel control and oversight team carries out monitoring and outreach activities to be able to participate in overseeing the distribution of fuel oil to all districts in Indonesia. Keywords: Policy Implementation, Oil Distribution, One Price JEL Classifications: D04, E64, Q31, R12 DOI: https://doi.org/10.32479/ijeep.8824